Aberrant Resting-State Cerebellar-Cerebral Functional Connectivity in Unmedicated Patients With Obsessive-Compulsive Disorder - Murayama, Keitaro; Tomiyama, Hirofumi; Tsuruta, Sae; Ohono, Aikana; Kang, Mingi; Hasuzawa, Suguru; Mizobe, Taro; Kato, Kenta; Togao, Osamu; Hiwatashi, Akio; Nakao, Tomohiro (Frontiers in Psychiatry, 2021)
Background: Although abnormality of cerebellar-cerebral functional connectivity at rest in obsessive-compulsive disorder (OCD) has been hypothesized, only a few studies have investigated the neural mechanism. To verify the findings of previous studies, a large sample of patients with OCD was studied because OCD shows possible heterogeneity. Methods: Forty-seven medication-free patients with OCD and 62 healthy controls (HCs) underwent resting-state functional magnetic imaging scans. Seed-based connectivity was examined to investigate differences in cerebellar-cerebral functional connectivity in OCD patients compared with HCs. Correlations between functional connectivity and the severity of obsessive-compulsive symptoms were analyzed. Results: In OCD, we found significantly increased functional connectivity between the right lobule Ⅵ and the left precuneus, which is a component of the default mode network (DMN), compared to HCs. However, there was no correlation between the connectivity of the right lobule Ⅵ-left precuneus and obsessive-compulsive severity. Conclusions: These findings suggest that altered functional connectivity between the cerebellum and DMN might cause changes in intrinsic large-scale brain networks related to the traits of OCD.